Analytical Capability of Defocused µ-SORS in the Chemical Interrogation of Thin Turbid Painted Layers. Issue 1 (January 2016) - Conti, Claudia; Realini, Marco; Botteon, Alessandra; Colombo, Chiara; Noll, Sarah; Elliott, Stephen R.; Matousek, Pavel
A recently developed micrometer-scale spatially offset Raman spectroscopy (μ-SORS) method provides a new analytical capability for investigating non-destructively the chemical composition of sub-surface, micrometer-scale thickness, diffusely scattering layers at depths beyond the reach of conventional confocal Raman microscopy. Here, we demonstrate experimentally, for the first time, the capability of μ-SORS to determine whether two detected chemical components originate from two separate layers or whether the two components are mixed together in a single layer. Such information is important in a number of areas, including conservation of cultural heritage objects, and is not available, for highly turbid media, from conventional Raman microscopy, where axial (confocal) scanning is not possible due to an inability to facilitate direct imaging within the highly scattering sample. This application constitutes an additional capability for μ-SORS in addition to its basic capacity to determine the overall chemical make-up of layers in a turbid system.